Efektivitas Layanan Referensi Didinas Kearsipan dan Perpustakaan Sumatera Barat - Rohid Aziz; Gustina Erlianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Reference services are one of the core services in regional public libraries, playing a strategic role in bridging the public's information needs with available resources. Amidst the development of information technology and the increasing complexity of users' information needs, libraries are required to provide reference services that are not only available conventionally, but also effective, responsive, and adaptive to changes in the information environment. However, in practice, reference services in regional libraries still face various challenges, including a limited number of competent reference librarians, low utilization of digital technology in reference services, and the lack of a structured and sustainable user satisfaction evaluation system. These conditions have the potential to hinder the optimization of libraries' functions as information-based public service institutions. This study aims to measure the effectiveness of reference services at the Archives and Library Service of West Sumatra Province using a quantitative approach. The research method used was a survey, with data collected through questionnaires distributed to users who actively use reference services. The research analysis framework is based on Richard M. Steers' theory of organizational effectiveness, which includes five main indicators: goal achievement, efficiency, integration, adaptation, and productivity. The data obtained were analyzed descriptively to obtain a comprehensive picture of the effectiveness of reference services. The results of the study indicate that reference services at the Archives and Library Service of West Sumatra Province are categorized as quite effective. Indicators of goal achievement and integration show relatively good results, while indicators of efficiency and adaptation still require improvement, particularly in the utilization of information technology and the development of digital-based reference services. This study concludes that increasing the effectiveness of reference services requires strengthening librarian competencies, optimizing the use of information technology, and implementing systematic and continuous service evaluation to improve the quality of public services in the library sector.